Apakah Live Shopping dan Diskon berpengaruh terhadap Keputusan Pembelian : Studi Kasus : Gen Z dan TikTok Shop - Rieke Alisyiya Nur Safitri; Rayhan Gunaningrat; Indra Hastuti (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
The development of social media and digital technology has driven changes in shopping behavior, especially among Generation Z. TikTok Shop is present as a platform for e-commerce that combines entertainment and shopping activities through live shopping features and various discount offers. This study aims to examine each contribution of some of the variables to be tested. This study applies a quantitative type. With a population of Generation Z who shop at TikTok Shop. through purposive sampling and a survey of 100 buyers. Purposive sampling is used as a technique to obtain samples. Data will be obtained from Google Form. Then analyze it from Partial Least Squares - Structural Equation Modeling assisted by SmartPLS 3.0. The resulting discounts and live shopping contribute to shopping decisions from simultaneous or partial. The implications of the results of this study provide an understanding for business actors and digital platform managers in designing an approach to increasing marketing efficiency and in accordance with the characteristics of today's digital consumers.